Kepuasan Pelayanan Publik Pada Kantor Pelayanan Perizinan Dan Penanaman Modal Kabupaten Temanggung - Eka Budi Setiawan; Edy Anan (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2015)
This study examined the effect of quality of service and service procedures to the satisfaction of the people in the Office of Licensing Services and Investment Kabupaten Temanggung. The variable quality of services consisting of officer discipline, officer responsibilities, personnel capabilities, speed of service, fairness, and courtesy and hospitality workers. While variable service procedures consist of the ease of service procedures, in common with the kind of service requirements, clarity and certainty, reasonableness of costs, compliance costs are set by paid, the accuracy of the time schedule service, environmental comfort, and security services. The population in this study are all the applicant's licensing services with a sample of 192 respondents were selected by accidental sampling method. The results showed that the index of satisfaction of the people who are in the good category, the best elements contained on politeness and friendliness officers and the lowest gain in speed of service elements. Hypothesis test results indicate that the quality and service procedures significantly positive effect on people's satisfaction in public service.